Teratoma-associated anti-N-methyl-D-aspartate receptor encephalitis: A case report and literature review - Yan, Bin; Wang, You; Zhang, Ying; Lou, Weihua (Medicine (Baltimore), 2019)
Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis is an autoimmune disease associated with the NMDA receptor and has a good response to treatment. However, only few cases related to teratoma have been reported. Here, we report a case of teratoma-associated anti-NMDAR encephalitis. A 25-year-old woman presenting with fever for 20 days and psychiatric symptoms for 9 days was admitted to the hospital. The patient progressed to a minimally conscious state consistent with encephalitis. Considering the possibility of autoantibody-mediated encephalitis, laboratory tests were conducted to detect anti-NMDAR antibodies in cerebrospinal fluid and serum. Results confirmed the diagnosis of anti-NMDAR encephalitis. Furthermore, gynecological ultrasound investigation detected teratoma in the left ovary. After resection of the teratoma with laparoscopic adnexectom, the patient was treatment with immunosuppressive therapy. The patient recovered gradually and was discharged 2 months after the operation. Anti-NMDAR encephalitis remains difficult to diagnose because of its vague manifestations, and no clinical practice guidelines for prevention and treatment of the disease have been established yet. The clinical data of a case of teratoma-related anti-NMDAR encephalitis were analyzed, and relevant studies were reviewed.